Evaluation of bio-efficacy of Metarhizium anisopliae against the pink bollworm Pectinophora gossypiella (Saunders), with insights into its colonization potential and insecticide compatibility - Snehal Thavkar; Shivaji Thube; Pramod Panchbhai; Nandkishor Lavhe; Tinni Pillai; Vivek Shah; Vrushali Deshmukh; Thavaprakasa R. Pandian; Babasaheb Fand; Prabhulinga Tenguri; Akash Nikoshe; Mhatre Priyank; et al. (Journal of Cotton Research)
Abstract Background The pink bollworm (Pectinophora gossypiella, PBW) is a major cotton pest, causing economic losses by damaging seeds and fiber. Cotton growers typically use systemic and broad-spectrum insecticides for its management, which pose risks to human health and the environment. Consequently, there is a need for eco-friendly alternatives. This study evaluates the bio-efficacy of the entomopathogenic fungus Metarhizium anisopliae strain TMBMA1 against pink bollworm and assesses its compatibility with major insecticides. Additionally, to comprehend the dynamics of colonization and the infection processes of entomopathogenic fungi (EPF), scanning electron microscopy (SEM) of infected larvae was carried out. Result We challenged the second instar PBW larvae to eight different concentrations (1 × 103 to 1 × 101 0 conidia mL−1) of an M. anisopliae strain TMBMA1. The highest mortality (100%) occurred at the higher concentrations i.e., 1 × 109 and 1 × 1010 spores mL−1, while the lowest mortality rate (46.6%) was observed at 1 × 103 spores mL−1 concentration compared to control (3.33%). TMBMA1's biocontrol efficacy was validated by Probit analysis, exhibiting an exceptionally low median lethal concentration (LC 50) value of 7.1 × 105. The comparative evaluation revealed that the M. anisopliae strain TMBMA1 performed excellently with insecticide [Cypermethrin 10% (volume fraction) emulsifiable concentrate (EC) at 1 mL·L−1 water] giving 100% mortality, both being superior to a commercial product of M. anisopliae (60%). According to SEM analysis, the EPF strain was profusely colonized on both the internal and external surfaces of PBW larvae. Compatibility studies with insecticides revealed > 98% and > 96% reduction in the sporulation of M. anisopliae due to the treatment of Emamectin Benzoate 1.5% (mass fraction) + Profenofos 35% (mass fraction) water dispersible granules (WDG) and Profenofos 50% EC, respectively. In contrast, Cypermethrin 10% EC, Emamectin Benzoate 5% (mass fraction) Soluble Granules and Neem Seed Kernel Extract (NSKE) 0.15% (volume fraction) treatments reported lower reduction (11.45%, 13.79% and 21.21% respectively) in spore production. Conclusion According to the current investigations, the M. anisopliae strain TMBMA1 exhibits high virulence against PBW and offers a promising eco-friendly solution for managing this pest. It shows significant potential to proliferate on both external and internal surfaces of PBW. This strain can be integrated into PBW management programs with chemical insecticides, improving pest control and lessening environmental impact.